Dietary Carbohydrate and Diverse Health Outcomes: Umbrella Review of 30 Systematic Reviews and Meta-Analyses of 281 Observational Studies - Liu, Ya-Shu; Wu, Qi-Jun; Lv, Jia-Le; Jiang, Yu-Ting; Sun, Hui; Xia, Yang; Chang, Qing; Zhao, Yu-Hong (Frontiers in Nutrition, 2021)
Background & Aims: The associations between dietary carbohydrate and diverse health outcomes remain controversial and confusing. To summarize the existing evidence of the association between dietary carbohydrate intake and diverse health outcomes and to evaluate the credibility of these sources of evidence. We performed this umbrella review of evidence from meta-analyses of observational studies. Methods: PubMed, Embase, Web of Science databases, and manual screening of references up to July 2020 were searched. Systematic reviews with meta-analyses of observational studies in humans investigating the association between dietary carbohydrate intake and multiple health outcomes were identified. We assessed the evidence levels by using summary effect sizes, 95% prediction intervals, between-study heterogeneity, evidence of small-study effects, and evidence of excess significance bias for each meta-analysis. Results: We included 43 meta-analyses of observational research studies with 23 health outcomes, including cancer (n=26), mortality (n=4), metabolic diseases (n=4), digestive system outcomes (n=3), and other outcomes (coronary heart disease [n=2], stroke [n=1], Parkinson’s disease [n=1], and bone fracture [n=2]). This umbrella review summarized 281 individual studies with 13,164,365 participants. Highly suggestive evidence of an association between dietary carbohydrate intake and metabolic syndrome was observed with adjusted summary odds ratio of 1.25 (95% confidence interval [CI] 1.15-1.37). The suggestive evidences were observed in associations of carbohydrate consumption with esophageal adenocarcinoma (0.57, 95% CI=0.42-0.78) and all-cause mortality (adjusted summary hazard ratio 1.19, 95% CI=1.09-1.30). Conclusions: Despite the fact that numerous systematic reviews and meta-analyses have explored the relationship between carbohydrate intake and diverse health outcomes, there is no convincing evidence of a clear role of carbohydrate intake. However, there is highly suggestive evidence suggested carbohydrate intake is associated with high risk of metabolic syndrome, suggestive evidence found its association with increased risk of all-cause mortality and decreased risk of esophageal adenocarcinoma. Systematic review registration: CRD42020197424.